Cardiac remodeling and arrhythmogenesis are ameliorated by administration of Cx43 mimetic peptide Gap27 in heart failure rats - Lucero, Claudia M.; Andrade, David C.; Toledo, Camilo; Diaz, Hugo S.; Pereyra, Katherin V.; Diaz-Jara, Esteban; Schwarz, Karla G.; Marcus, Noah J.; Retamal, Mauricio A.; Quintanilla, Rodrigo A.; Del Rio, Rodrigo (My University, 2020)
Alterations in connexins and specifically in 43 isoform (Cx43) in the heart have been associated with a high incidence of arrhythmogenesis and sudden death in several cardiac diseases. We propose to determine salutary effect of Cx43 mimetic peptide Gap27 in the progression of heart failure. High-output heart failure was induced by volume overload using the arterio-venous fistula model (AV-Shunt) in adult male rats. Four weeks after AV-Shunt surgery, the Cx43 mimetic peptide Gap27 or scrambled peptide, were administered via osmotic minipumps (AV-Shunt(Gap27) or AV-Shunt(Scr)) for 4 weeks. Cardiac volumes, arrhythmias, function and remodeling were determined at 8 weeks after AV-Shunt surgeries. At 8(th) week, AV-Shunt(Gap27) showed a marked decrease in the progression of cardiac deterioration and showed a significant improvement in cardiac functions measured by intraventricular pressure-volume loops. Furthermore, AV-Shunt(Gap27) showed less cardiac arrhythmogenesis and cardiac hypertrophy index compared to AV-Shunt(Scr). Gap27 treatment results in no change Cx43 expression in the heart of AV-Shunt rats. Our results strongly suggest that Cx43 play a pivotal role in the progression of cardiac dysfunction and arrhythmogenesis in high-output heart failure; furthermore, support the use of Cx43 mimetic peptide Gap27 as an effective therapeutic tool to reduce the progression of cardiac dysfunction in high-output heart failure.
Keywords: Volume overload; Ventricular remodeling